Validity of self reports in a cohort of Swedish adolescent smokers and smokeless tobacco (snus) users. Issue 2 (24th March 2005) - Post, A; Gilljam, H; Rosendahl, I; Meurling, L; Bremberg, S; Galanti, M R
Abstract : Objective: To validate self reports of cigarette and smokeless tobacco (snus) use in a prospective cohort of adolescents. Design: A cross sectional analysis of a cohort sub-sample. Setting: County of Stockholm, Sweden. Subjects: 520 adolescents in the final grade of junior high school (mean age 15.0 years). Main outcome measure: Concordance between self reported tobacco use and saliva cotinine concentration. Results: Using a cut point of 5 ng/ml saliva cotinine to discriminate active tobacco use, there was a 98% concordance between self reported non-use in the past month and cotinine concentration. The sensitivity of the questionnaire compared to the saliva cotinine test, used as the gold standard, was 90% and the specificity 93%. One hundred and fifteen out of 520 subjects (22%) reported monthly tobacco use. Among these, 67% (46/69) of the exclusive cigarette smokers, 82% (23/28) of exclusive snus users, and 94% (15/16) of mixed users (cigarettes + snus) had cotinine concentrations above 5 ng/ml. Among subjects reporting daily use 96% (64/67) had saliva cotinine concentrations above the cut point. Exclusive current cigarette users were more likely to be classified discordantly by questionnaire and cotinine test compared to snus users (odds ratio 3.2, 95% confidence interval 1.2 to 8.6). Conclusion: This study confirms the reliability of adolescents' self reported tobacco use. In a context of low exposure to environmental tobacco smoke a cut off for saliva cotinine of 5 ng/ml reliably discriminated tobacco users from non-users. Irregular use of tobacco in this age group probably explains the discrepancy between self reported use and cotinine concentrations.